Fine Boys - Imasuen, Eghosa (Nigeria, 2011)
Ewaen is bored at home in Warri and eager to flee from his parents' incessant quarrelling. When he and his friends gain admission into the University of Benin months later, they meet new friends, boys and girls who, like him, are excited about their newfound independence. They hang out in parking lots, trading jibes and learning to navigate the unpredictable staff strikes and mayhem unleashed on their campus by ruthless confraternities who are always on the lookout for new recruits...
Keywords: Fiction